PENGARUH PELAYANAN DAN SISTEM MUDHARABAH TERHADAP KEPUTUSAN NASABAH MENABUNG - Siti Hariza; Mohammad Usman (I'THISOM : Jurnal Ekonomi Syariah, 2022)
BMT Syariah Mawaddah Karang Penang Branch Sampang Madura with service activity programs with the mudharabah system in customer decisions to save there is a significant effect simultaneously, but partially only the mudharabah system has a significant effect.The purpose of this study is to determine the effect of the service and the mudharabah system on the customer's decision to save simultaneously, to determine the effect of the service and the mudharabah system to the customer's decision to save partially, to determine the influence of the dominant variable from the independent variable that affects the independent variable. This research is quantitative research with data analysis technique using multiple linear regression. The data used in the form of primary data through the distribution of questionnaires to customers of BMT Syariah Mawaddah Karang Penang Branch Sampang Madura in 2021. The sample used in this study was 83 respondents. The results of this study indicate that (1) the service and the mudharabah system simultaneously have a significant effect on the customer's decision to save by 0.050. (2) Service partially has no significant effect on the customer's decision to save by 0.282. (3) the mudharabah system partially has a significant effect on the customer's decision to save by 0.083